International Ocean Discovery Program Expedition 392 preliminary report: Agulhas Plateau Cretaceous Climate: drilling the Agulhas Plateau and Transkei Basin to reconstruct the Cretaceous–Paleogene tectonic and climatic evolution of the Southern Ocean basin - Uenzelmann-Neben, G; Bohaty, SM; Childress, LB; Archontikis, OA (International Ocean Discovery Program, 2022)
During International Ocean Discovery Program Expedition 392, three sites were drilled on the Agulhas Plateau and one site was drilled in the Transkei Basin in the Southwest Indian Ocean. This region was positioned at paleolatitudes of ~53°–61°S during the Late Cretaceous (van Hinsbergen et al., 2015) (100–66 Ma) and within the new and evolving gateway between the South Atlantic, Southern Ocean, and southern Indian Ocean basins. Recovery of basement rocks and sedimentary sequences from the Agulhas Plateau sites and a thick sedimentary sequence in the Transkei Basin provides a wealth of new data to (1) determine the nature and origin of the Agulhas Plateau; (2) significantly advance the understanding of how Cretaceous temperatures, ocean circulation, and sedimentation patterns evolved as CO2 levels rose and fell and the breakup of Gondwana progressed; (3) document long-term paleoceanographic variability through the Late Cretaceous and Paleogene; and (4) investigate geochemical interactions between igneous rocks, sediments, and pore waters through the life cycle of a large igneous province (LIP). Importantly, postcruise analysis of Expedition 392 drill cores will allow testing of competing hypotheses concerning Agulhas Plateau LIP formation and the role of deep ocean circulation changes through southern gateways in controlling Late Cretaceous–early Paleogene climate evolution.